A high oxidation resistance Ti2AlC coating on Zirlo substrates for loss-of-coolant accident conditions. Issue 11 (1st August 2019) - Li, Wentao; Wang, Zhenyu; Shuai, Jintao; Xu, Beibei; Wang, Aiying; Ke, Peiling
Abstract: After Fukushima nuclear accident, the concept of ATFs cladding coating was proposed in order to provide more rescue time under accident conditions. In this work, we fabricated the dense Ti2 AlC MAX phase coatings on Zirlo substrate using a hybrid arc/magnetron sputtering technique followed by an annealing treatment. Mechanical properties of the Ti2 AlC coating was evaluated, and its oxidation resistance in pure steam conditions was particularly investigated at 1000 °C, 1100 °C and 1200 °C under different oxidation times. The results showed that Ti2 AlC coating presents the higher hardness and elastic modulus than substrate, which can effectively improve the mechanical properties of bare Zirlo substrates. The high-temperature oxidation resistance of the Zirlo substrate in pure steam was significantly improved by the coatings with a compact structure and the formed triple scale oxide scale (α-Al2 O3 +RTiO2 /α-Al2 O3 /TiO2 ) during oxidation process. The presented Ti2 AlC MAX phase coatings with a facile hybrid arc/sputtering technique enable them a promising candidate as oxidation protective coatings for ATF claddings.